CARE BETWEEN GAY PEOPLE WITH IMMUNODEFICIENCY VIRUS (HIV) HUMAN IN COMPLIANCE WITH ARV THERAPY IN PUZZLE INDONESIAN PUZZLE INSTITUTION KELURAHAN BABAKAN SARI KECAMATAN KIARACONDONG, BANDUNG CITY - Sugiantoro Sugiantoro; Lina Favourita Sutiaputri (Politeknik Kesejahteraan Sosial Bandung, 2019)
Concern is a concern, empathy to maintain relationships with others in the form of mutual respect and feeling of ownership and responsibility given to problems solving faced by others. This study aims to obtain an empirical description of: 1) the characteristics of respondents, 2) the concerns of respondents to fellow gay HIV sufferers from the aspect of understanding, 3) respondents 'awareness of fellow gay HIV sufferers from the aspect of awareness, 4) respondents' awareness of fellow gay HIV sufferers from the aspect of ability. The research method used in this study is a quantitative research method using descriptive surveys. Data collection techniques used in this study were questionnaires and documentation studies. The validity test used in this study is face validity and reliability testing using the Cronbach Alpha formula. The results of research on HIV gay care among adherents of ARV therapy in Lembaga Swadaya Masyarakat Puzzle Indonesia Babakan Sari Sub-district, Kiaracondong District, Bandung City showed that the level of care among fellow gay HIV sufferers in adhering to ARV therapy was in the moderate category. Concern of respondents towards fellow gay HIV sufferers in the understanding aspect entered into the high category. Two other aspects are awareness and ability in the medium category. The program proposed to answer the problems that arise in this research is